Students’ Perceptions of the Influence of Anti-Violence Value Internalization on Prosocial Behavior in Social Studies Learning - Hikmah Wifaqi; Nur Ali; Dwi Sulistiani (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2026)
This study responds to the increasing incidence of school violence by examining the role of anti-violence values in fostering students’ prosocial behavior through Social Studies learning. An exploratory sequential mixed-methods design was employed. The qualitative phase involved interviews, observations, and document analysis with eighth-grade students at Al-Hikmah IIBS Batu Junior High School. The quantitative phase involved 38 students selected through total sampling and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS. The findings revealed that students perceived the internalization of anti-violence values positively, as reflected in prosocial behaviors such as sharing, cooperation, helping, and donating during learning activities. The measurement model demonstrated satisfactory validity and reliability, while the structural model indicated that the internalization of anti-violence values had a positive and significant effect on students’ prosocial behavior. These results suggest that integrating anti-violence values into Social Studies learning contributes to the development of prosocial behavior and supports violence prevention efforts in schools. The study highlights the importance of value-based learning in creating a safe and supportive educational environment.